2010
DOI: 10.1007/s11104-010-0352-z
|View full text |Cite
|
Sign up to set email alerts
|

Soil organic carbon fractions differ in two contrasting tall fescue systems

Abstract: The value of tall fescue (Festuca arundinacea Schreb.) for C sequestration in addition to forage production and soil conservation is of current interest. However, studies relating to the impacts of endophyte infected (E+) and endophyte free (E−) tall fescue on soil organic matter fractions are few. This study examined how E+ and E− growth affected soil C fractions 4 years after establishment. The study site was at

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
8
0
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(10 citation statements)
references
References 46 publications
1
8
0
1
Order By: Relevance
“…Carbon released from plant roots, depending on the chemical form, can be rapidly mineralized (0.5–2 h) by the rhizosphere microbial community, and/or incorporated into microbial biomass where it can persist for longer time periods (30–90 days) (Jones et al, 2004 ). Several studies have reported increases in C and N in pasture soils throughout the southeastern United States under CTE+ compared to E- infected tall fescue (Franzluebbers et al, 1999b ; Franzluebbers and Stuedemann, 2005 ; Iqbal et al, 2012 ), although in other studies the same trend was not observed (Handayani et al, 2011 ). If endophyte-associated changes to root exudation mediate the observed alterations to total C and N pools, the fact that we observed increased total C exudation in CTE+/97TF1 but not CTE+/PDF suggests that the conflicting reports may be related to different cultivars being examined.…”
Section: Discussionmentioning
confidence: 91%
“…Carbon released from plant roots, depending on the chemical form, can be rapidly mineralized (0.5–2 h) by the rhizosphere microbial community, and/or incorporated into microbial biomass where it can persist for longer time periods (30–90 days) (Jones et al, 2004 ). Several studies have reported increases in C and N in pasture soils throughout the southeastern United States under CTE+ compared to E- infected tall fescue (Franzluebbers et al, 1999b ; Franzluebbers and Stuedemann, 2005 ; Iqbal et al, 2012 ), although in other studies the same trend was not observed (Handayani et al, 2011 ). If endophyte-associated changes to root exudation mediate the observed alterations to total C and N pools, the fact that we observed increased total C exudation in CTE+/97TF1 but not CTE+/PDF suggests that the conflicting reports may be related to different cultivars being examined.…”
Section: Discussionmentioning
confidence: 91%
“…When 8 to 15 year-old tall fescue pastures had high endophyte infection levels, potential C mineralization per unit of soil organic C was lower than when endophyte infection levels were low (Franzluebbers et al 1999). At the end of 4 years of seed-harvest management of tall fescue in Kentucky, potential C mineralization per unit of microbial biomass C was lower under E+ than under E− tall fescue (Handayani et al 2010). Leaf litter from E+ tall fescue decomposed slower than from E− tall fescue throughout a 24-week litter-bag study (Siegrist et al 2010).…”
mentioning
confidence: 92%
“…Organic C Increased [149,153] Carbohydrates Increased [149] Phenols Increased [150] Organic Matter Increased [153] Microbial Biomass C Mixed Results [147,154] Mineralizable C Decreased [147,154] Microbial Biomass N Increased [147] Mineralizable N Increased was diseased with Verticillium, it was found that beneficial bacteria and fungi were greatly reduced and saprophytic fungi were increased [162]. Similarly, aphid infestation of the aerial parts of pepper plants led to root exudation composition changes to recruit bacteria that aided in aphid susceptibility [163].…”
Section: Soil Component E+ Effect Referencementioning
confidence: 98%
“…C sequestration is the ability of the soil to fix atmospheric C. This provides important environmental effects as well as providing an essential nutrient to the plant and soil microorganisms. Handayani et al [154] looked at C levels in the two tall fescue systems over the course of four years. They took data on microbial biomass, particulate organic matter C, microbial biomass C, mineralizable C, and C in micro and macro aggregates.…”
Section: Epichloe Effect On the Rhizospherementioning
confidence: 99%